2020
DOI: 10.1080/0886022x.2020.1811121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxia-inducible factor-prolyl hydroxylase inhibitors on anemia in patients with CKD: a meta-analysis of randomized controlled trials including 2804 patients

Abstract: (2020) Effect of hypoxia-inducible factor-prolyl hydroxylase inhibitors on anemia in patients with CKD: a metaanalysis of randomized controlled trials including 2804 patients,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 56 publications
1
39
0
Order By: Relevance
“…By inhibiting PHD, the agents stabilize HIF‐α that results in increased HIF transcriptional activity, which can stimulate the synthesis of endogenous EPO from native kidneys or the liver and regulate iron metabolism 12 . Previous systematic reviews and meta‐analyses based on small‐sample clinical data proved that short‐term use of HIF‐PHD inhibitors increased haemoglobin levels in anaemic patients with CKD and reached different conclusions on iron parameters and adverse event profiles 13,14 . Now, we performed a comprehensive meta‐analysis to further assess the long‐term efficacy and safety of HIF‐PHD inhibitors for the treatment of anaemia in CKD.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…By inhibiting PHD, the agents stabilize HIF‐α that results in increased HIF transcriptional activity, which can stimulate the synthesis of endogenous EPO from native kidneys or the liver and regulate iron metabolism 12 . Previous systematic reviews and meta‐analyses based on small‐sample clinical data proved that short‐term use of HIF‐PHD inhibitors increased haemoglobin levels in anaemic patients with CKD and reached different conclusions on iron parameters and adverse event profiles 13,14 . Now, we performed a comprehensive meta‐analysis to further assess the long‐term efficacy and safety of HIF‐PHD inhibitors for the treatment of anaemia in CKD.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…The hypoxia response pathway, when activated by hypoxia, minimizes such damage; however, long-term adaptations and tissue remodeling triggered by the hypoxia response pathway itself can also cause damage 5,6 . The pathway can also be activated to promote anaerobic glycolysis (i.e., the Warburg effect) even under aerobic conditions, including in some cancers, in dividing stem cells, in the proliferation of activated T lymphocytes, during endometrial decidualization, and presumably in patients receiving prolyl hydroxylase inhibitors to treat anemia associated with chronic kidney disease 1,[7][8][9][10][11][12][13][14][15][16][17] . HIF-1 clearly upregulates enzymes that mediate anaerobic glycolysis, but our understanding of the complete adaptive response mobilized by pathway activation has largely focused on gene expression changes in cultured cells [18][19][20][21] .…”
Section: Main Textmentioning
confidence: 99%
“…However, patients treated with ESAs are exposed to supraphysiologic EPO concentrations, potentially leading to adverse events [ 5 , 37 , 43 , 44 ]. Some studies have found an increased risk of cardiovascular events and stroke in both hemodialysis-dependent and nonhemodialysis-dependent patients targeted at higher Hb levels [ 45 , 46 ].…”
Section: Erythropoiesis-stimulating Agentsmentioning
confidence: 99%
“…The prevalence of renal anemia gradually rises as the estimated glomerular filtration rate (eGFR) decreases [ 3 ]. Anemia occurs in approximately half of patients with CKD stage G4 and in more than 90% of the end-stage renal disease patients who undergo dialysis [ 3 , 4 , 5 ]. Correcting renal anemia can decrease mortality, hospitalization, risk of CKD progression, and improve the health-related quality of life [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation